Yaws in the Western Pacific Region: A Review of the Literature - Corinne Capuano; Masayo Ozaki (Journal of Tropical Medicine)
Until the middle of the 20th century, yaws was highly endemic and considered a serious public health problem in the Western Pacific Region (WPR), leading to intensive control efforts in the 1950s–1960s. Since then, little attention has been paid to its reemergence. Its current burden is unknown. This paper presents the results of an extensive literature review, focusing on yaws in the South Pacific. Available records suggest that the region remains largely free of yaws except for Papua New Guinea, Solomon Islands, and Vanuatu. Many clinical cases reported recently were described as “attenuated”; advanced stages are rare. A single intramuscular injection of benzathine penicillin is still effective in curing yaws. In the Pacific, yaws may be amenable to elimination if adequate resources are provided and political commitment revived. A mapping of yaws prevalence in PNG, Solomon, and Vanuatu is needed before comprehensive country-tailored strategies towards yaws elimination can be developed.